Antecedents of service recovery towards customer satisfaction in Kota Kinabalu City Hall / Nur Aishah Basar - Basar, Nur Aishah (2015)
This research aims to identify the service recovery justices that may influence customer satisfaction in Kota Kinabalu City Hall. The service recovery justice that being focused is the interactional justice consists of apology, explanation and effort and courtesy. Each of the justices will be tested to see whether it influences the satisfaction of the customers. The objective of this study is to identify whether apology can influence customer satisfaction in Kota Kinabalu City Hall to identify whether explanation and effort can influence customer satisfaction in Kota Kinabalu City Hall, to identify whether courtesy can influence customer satisfaction in Kota Kinabalu City Hall and to identify the main justice that will influence customer satisfaction in Kota Kinabalu City Hall. Questionnaires were distributed to 384 respondents in Kota Kinabalu City. The findings that are gained from this research are tested using statistical package for social science (SPSS) version 21.0. Findings indicates that all justices are significant, however the highest significant towards customer satisfaction is explanation and effort. The implication of each variables and recommendation for further research is identified and proposed in this thesis.